Designing 'Realistic' Healthcare Improvement. (21st May 2020) - Inns, Tom; Mountain, Rod
Abstract : Realistic Medicine asks that both clinicians and patients pause, reflect, and get back to the basic principles of compassionate care. A program in Scotland shows what can be accomplished when health care professionals used design principles to improve the experience for patients and caregivers.